2018
DOI: 10.1063/1.5039405
|View full text |Cite
|
Sign up to set email alerts
|

Lower-hybrid drift instability and macroscopic flow of colliding magnetized plasmas

Abstract: Microscopic instability and macroscopic flow pattern resulting from colliding plasmas are studied analytically in support of laboratory experiments. The plasma flows are assumed to stream radially from two separate centers. In a quasi-planar (2D) geometry, they may arise from an Ohmic explosion of two parallel wires, but similar configurations emerge from other outflows, e.g., colliding winds in binary star systems. One objective of this paper is to characterize the flow instabilities developing near the flow … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…Spatio-temporal characteristics of the instabilities and associated turbulent motion is another objective of this study. The analytic and numerical studies in [1,2] have indicated that plasmas that stream against each other from two ohmically vaporized wires may indeed mix in a relatively thin layer, in accord with the preceding experiments [5]. The shocked corona layer is separated from the inflowing material by a pair of termination shocks (for supersonic flows), and the plasma pressure inside the layer reaches its maximum at the flow stagnation point.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…Spatio-temporal characteristics of the instabilities and associated turbulent motion is another objective of this study. The analytic and numerical studies in [1,2] have indicated that plasmas that stream against each other from two ohmically vaporized wires may indeed mix in a relatively thin layer, in accord with the preceding experiments [5]. The shocked corona layer is separated from the inflowing material by a pair of termination shocks (for supersonic flows), and the plasma pressure inside the layer reaches its maximum at the flow stagnation point.…”
Section: Introductionsupporting
confidence: 67%
“…To produce such deflection, the electrostatic potential, Φ, must reach the level of where u is the speed of plasma upstream of the collision layer, and M is the ion mass. In more detail, a twodimensional flow that emerges from the collision of two concentric outflows has been studied using the hodograph transformation in [1]. The magnetic field carried to the collision layer with the flows is assumed to have no substantial effect on the ion motion since the flow ram pressure is typically about an order of magnitude higher than the magnetic pressure [5].…”
Section: Two-stream Instability In Counterstreaming Plasmasmentioning
confidence: 99%
See 3 more Smart Citations